Efficacy of topical and systemic treatments for atopic dermatitis on pruritus: A systematic literature review and meta-analysis - Rodriguez-Le Roy, Youna; Ficheux, Anne-Sophie; Misery, Laurent; Brenaut, Emilie (Frontiers in Medicine, 2022)
Pruritus is a major and burdensome symptom in atopic dermatitis (AD). The number of systemic treatments available for AD has increased recently, enabling improved patient relief. To evaluate the effect of AD treatments on pruritus. A systematic literature review and a meta-analysis were conducted to evaluate and compare the effects of treatment used in AD on pruritus. PubMed and Embase databases were searched to find articles published between January 1990 and December 2021.Topical and systemic treatments were studied in patients aged ≥10 years. Among the 448 articles identified, 56 studies were retained in the systematic review. 15 studies evaluated topical treatments: topical corticosteroids (TCS; 2), calcineurin inhibitors (6), PDE4 inhibitors (3), and Jak inhibitors (4). 5 studies were included in the meta- analysis. All treatments had a positive effect on pruritus, with a mean overall reduction of 3.32/10, 95%IC [2.32- 4.33]. The greatest reduction was observed with halometasone (mean: 4.75), followed by tofacitinib 2% (mean: 4.38). 41 studies evaluated systemic therapies: cyclosporine (6), phototherapy (5), azathioprine (2), dupilumab (9), anti-IL13 (5), nemolizumab (3), Jak inhibitors (9), mepolizumab (1), and apremilast (1). 17 studies were included in 2 meta-analyses according to the concomitant use or not of TCS. In the meta-analysis without TCS, the overall decrease was 3.07/10, 95%IC [2.58-3.56]. The molecules with the highest efficacy on pruritus were upadacitinib 30 mg (mean: 4.90) and nemolizumab (mean: 4.81). Discussion : The therapeutic arsenal for AD has increased rapidly, and many molecules are under development. The primary endpoint of clinical trials is most often a score that assesses the severity of AD; however, the assessment of pruritus is also essential. The majority of molecules have a positive effect on pruritus, but the improvement varies between them. Efficacy on pruritus is not always correlated with efficacy on AD lesions; therefore, these two criteria are crucial to evaluate. The limitations of this study were the heterogeneity in the assessment of pruritus, the moment of the assessment, and the concomitant application of TCS or not for studies evaluating systemics. In the future, it would be useful to use standardized criteria for assessing pruritus.